1993
DOI: 10.1115/1.2910690
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convective Heat Transfer in a Divided Vertical Channel: Part II—Experimental Study

Abstract: An interferometric study has been conducted on two-dimensional laminar natural convection heat transfer in an isothermal vertical divided channel. Interferograms were obtained for air and a plate-to-channel length ratio of Lp/Lc= 1/3. Data are presented for the dividing plate located at the bottom (Li/Lc = 0) and top of the channel (Li/Lc=2/3). Comparisons of local and average Nusselt numbers are made with the numerical predictions from Part I. Although the experimental average Nusselt numbers are typically ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the case of a divided channel, comparisons of local and average wall Nusselt numbers, mass flow rates, and average channel Nusselt number were made with those given numerically and experimentally by Naylor and Tarasuk (1993a, b). In all cases, the present calculations gave identical results.…”
Section: Code Validationmentioning
confidence: 71%
See 2 more Smart Citations
“…In the case of a divided channel, comparisons of local and average wall Nusselt numbers, mass flow rates, and average channel Nusselt number were made with those given numerically and experimentally by Naylor and Tarasuk (1993a, b). In all cases, the present calculations gave identical results.…”
Section: Code Validationmentioning
confidence: 71%
“…Next, natural convection heat transfer in a divided vertical channel was considered. The solutions obtained for a divided vertical channel are compared with those of Naylor and Tarasuk (1993a, b).…”
Section: Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest average Nusselt number for complete system (channel and plate as a whole) was obtained by positioning the plate at the bottom of the channel. The experimental study [29] was obtained by means of a Mach-Zehender interferometer and the auxiliary plate was located at the bottom and top of the channel and its dimensionless height was 1/3. Experimental and numerical results were in good agreement even if the experimentally measured average Nusselt numbers were about 10% lower than the numerical results.…”
Section: Introductionmentioning
confidence: 99%
“…[28] and experimentally in Ref. [29]. The numerical study [28] showed that the heat transfer rate from the auxiliary plate can be significantly enhanced by the presence of the channel walls.…”
Section: Introductionmentioning
confidence: 99%